Insight into noncanonical small noncoding RNAs in Influenza A virus infection - Eun-A Ko; Tong Zhou; Jae-Hong Ko (Virus Research)
Influenza A virus (IAV) induces acute respiratory infections in birds and various mammals, including humans, and presents a significant global public health concern, with considerable economic consequences. Recently, researchers have shown keen interest in noncanonical small noncoding RNAs (sncRNAs) as carriers of epigenetic information, including tRNA-derived small RNAs (tsRNAs), rRNA-derived small RNA (rsRNAs), and Y RNA-derived small RNAs (ysRNAs). Particularly, tsRNAs and rsRNAs are detected in diverse species and demonstrate evolutionary conservation. We analyzed sncRNAs sequencing data in the pulmonary tissue of two genetically distinct mouse strains, C57BL/6J and DBA/2J, to explore strain-specific variations of sncRNAs in response to IAV infection. We systematically compiled information on noncanonical sncRNAs in these two strains and investigated the tsRNAs/rsRNAs/ysRNAs profiles influenced by IAV infection. Specifically, four noncanonical sncRNA families, including rsRNA-12S, GtsRNA-Arg-CCT, GtsRNA-Arg-TCT, and GtsRNA-Lys-TTT, exhibited upregulation upon IAV infection. Notably, DBA/2J mice showed earlier systemic differential expression of noncanonical sncRNAs after IAV infection compared to C57BL/6J mice. Additionally, our study revealed a strain-specific biogenesis of MtsRNAs in response to IAV infection. Also, distinct co-expression patterns of MtsRNAs were observed between C57BL/6J and DBA/2J mice, with DBA/2J mice showing broader positive co-expression of MtsRNAs with various sncRNA families compared to C57BL/6J mice. Our study provides a novel insight into noncanonical sncRNAs and their implications in IAV pathology and mouse strain specificity.